Evaluation of superimposed bending behaviour of laminated channel beams in modular steel buildings subjected to lateral load. (June 2022) - Xu, Bo; Xia, Junwu; Chang, Hongfei; Ma, Renwei; Zhang, Lihai
Abstract: The cooperation between adjacent floor and ceiling beams has been verified to effectively enhance the seismic performance of modular steel buildings. However, the structural performance of laminated double beam in the modular steel building subjected to lateral load has not been fully understood. In this study, the lateral tests, simplified finite element simulations, and theoretical derivations were conducted to systematically evaluate the superimposed bending behaviour of laminated channel beams under lateral loads. The results showed that the moment of inertia and interfacial shearing stiffness of the laminated beams were enhanced with the increase in the ceiling beam size and mechanical connector, and thereby the antisymmetric flexural properties of the double beam structures were enhanced. The strain neutral axes of the floor and ceiling layers deviated to the interface for the strongly laminated beams with interfacial bolt connections, indicating superimposition of these double beams. The interfacial slips, characterized by a symmetric parabola distribution mode, highly affected the combined action of the laminated channel beams. The remarkable increase in the slip-load rate led to yielding development of the laminated beams in modular steel buildings. Most importantly, analytical models for the effective bending stiffness were established considering the strain neutral axes deviation, which could quantify the superimposition effect of laminated beams subjected to lateral load. Highlights: Superimposed bending response of modular laminated steel beams subjected to lateral load was comprehensively evaluated. Increase in height ratio and interfacial connection promoted cooperative flexural properties of double beam structures. Deviation of strain neutral axes of layers was typical indicator of superimposition of laminated beams. Interfacial slip development and its influence on antisymmetric flexural performance of laminated beams were revealed. Analytical models of effective bending stiffness were established for laminated beams subjected to lateral load.